Conversion of DON to 3-epi-DON in vitro and toxicity reduction of DON in vivo by Lactobacillus rhamnosus. Issue 5 (3rd May 2019) - Qu, Rui; Jiang, Chunmei; Wu, Wanqin; Pang, Bing; Lei, Shuzhen; Lian, Ziyang; Shao, Dongyan; Jin, Mingliang; Shi, Junling
Abstract : Lactobacillus rhamnosus can convert DON to 3- epi -DON in vitro and reduce DON toxicity in vivo . Abstract : Deoxynivalenol (DON) is a mycotoxin that contaminates grains and feed. Degradation and toxicity reduction of DON by probiotics benefit human and animal health. Lactobacillus rhamnosus is an FDA-approved probiotic that can be used in children. After screening seven L. rhamnosus strains isolated from human milk, SHA113 showed the highest DON degradation rate of 60% under the optimal conditions of 37 °C, pH 6.0, OD600 = 1.5, 5 mg L −1 DON, and 48 h. When dead and live SHA113 cells were used separately, only the live cells reduced the DON concentration and transformed it into 3- epi -DON. Mice feeding experiments showed that pretreatment with SHA113 for 48 h reduced the toxicity of DON to the immunological system and organs. Directly feeding SHA113 cells could also slightly reduce the DON toxicity. Both in vitro and in vivo experiments indicated that L. rhamnosus has potential to reduce DON toxicity.